(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Budesonide and formoterol fumarate pressurized metered-dose inhaler (pMDI) is combined aerosol dosage form. The label claim of this combined dosage form is 100 mcg of Budesonide and 6 mcg of Formoterol Fumarate per actuation. It is prescribed for the treatment of asthma and chronic obstructive pulmonary disease (COPD). Formoterol fumarate is an anti-asthmatic drug (Bronchodilator), and Budesonide is Anti Inflammatory drug (Glucocortico steroid).The objective of plume geometry and spray pattern study is to monitor the consistency and quality of a device when actuated. The plume and pattern study aims to develop a formulation with robust device which can deliver an accurate amount of drug directly to the lungs of a patient. The chemistry manufacturing and controls (CMC) guideline outlined the basic data required for spray pattern and plume geometry measurement for different pMDI devices. In 2013, draft guidance on bioavailability and bioequivalence (BABE) of pMDI published, which provides details on plume geometry and spray pattern, image collection and evaluation.In the present study, the spray patterns were collected at 2 distances 3 and 6 cm from the actuator device's exit. The spray pattern Ovality results at 3 cm show 2.52% variation and at 6 cm results show 4.31% variation. Method precision, ruggedness and robustness study for Spray pattern also performed at 6 cm distance from actuator orifice. The plume geometry was collected at 6 cm distance from the exit of an actuator device. Plume geometry results show that Plume height is found in the range 16.20 cm to 18.98 cm, Plume angle is found from 17.7–24.9°, and Plume width is found between 3.68 to 4.57 cm.